GaN Based Cycloconverter-Type Dual-Active Bridge Converter: Control, Design, Analysis, and Experimental Verification - Gareau, Jacob (My University, 2020)
In recent years, there has been a greater push to reduce green house gas emissions due to the looming threat of climate change. This has resulted in a shift towards more electrified transportation and as a result, reliance on renewable energy such as solar or wind and a decreased reliance on fossil fuels. Battery energy storage systems (BESS) have been one of the prevailing methods for storing electrical energy from intermittent energy sources due to their performance, cost and size. However, in order to interface BESS with the AC power grid, power electronics are a necessity. With this paradigm shift from fossil fuels to renewable energy, power electronics and their components have been a large focus of research in the scientific community. There has been a trend for continuous improvement of power electronic converter performance which has led to the desire for advances in semiconductor switches. Switches with lower power loss would allow power electronic systems to achieve higher efficiency and higher power density. Due to the continuous desire for improvement, researchers have begun to adopt Wide-bandgap (WBG) switching devices since silicon (Si) has been reaching its material limit and WBG devices offer improved performance. Silicon carbide (SiC) and gallium nitride (GaN) offer improved performance over Si, GaN in particular offers the fastest switching speeds and based on the device rating is well suited for medium power levels in BESS. Although the potential of GaN is known, it is a fairly new technology and therefore a full analysis of its loss behaviour is required in order to model the device. In addition, GaN requires advanced measurement technologies to analyze them due to the high frequency operation and tiny device parasitics. Before GaN can reach widespread adoption in power electronic converters, the detailed analysis of the theoretical loss breakdown of a GaN-based power electronic system and measurement is required. The incorporation of GaN into isolated DC/AC converters necessary for interfacing the AC grid with the DC battery has the potential to increase the power density and efficiency. However, incorporating GaN alone can not fix all the current problems in the conventional design approach of two-stage cascaded Dual-active bridge (DAB) and inverters. Typically, the DAB and inverter are connected through an intermediate DC bus which requires large and unreliable electrolytic capacitors to filter the ripple power, these capacitors reduce the life-time of the converter significantly. This thesis proposes a GaN based single-stage DC/AC converter which does not require the large electrolytic capacitors or additional devices to filter the ripple power. In order to control the converter, a combined duty and phase shift control method is used. The operating condition for each discretized voltage output is derived based on the calculation for the lowest power loss conditions. To further investigate the proposed control and use of GaN, a greater focus on gate driver and PCB design is needed to take advantage of the new WBG switching devices such as GaN HEMTs. As switching frequencies are continuously pushed higher and higher to improve the power density of converters, there is a need for extremely fast turn on and turn off times for FETs in order to minimize losses and maximize efficiency. However, large slew rates have a negative impact on the circuit because the small parasitics present in the device packaging and PCB traces are no longer negligible and can result in severe oscillations and voltage spikes that can lead to increased losses or even device failure. Analysis of gate driver design and potential issues for designing with GaN are presented before the prototype is presented and analysed. A single-stage isolated DC/AC converter using GaN is shown to provide superior performance compared with the traditional two-stage approach. Simulation comparisons of both converters reveal that the proposed topology greatly improves efficiency while also removing the intermediate DC bus which is known to cause reliability issues. The efficiency improvement is achieved through a proposed control scheme that determines the duty and phase shift for each discretized output voltage based on a weighting equation for minimum losses. The control scheme and converter behaviour are both validated through the use of a experimental prototype.